Understanding da’wah and khatib - Saputra, Eko Hendro; Ghazali, M. Bahri; Mukmin, Hasan; Wiranto, Bambang Budi; Yanti, Fitri (Linguistics and Culture Review, 2021)
This paper presents understanding da’wah and khatib. Da'wah contains the meaning of an activity to invite people in a wise way to the right path for good, whether in oral, written, or deed, which is done consciously and planned in an effort to achieve welfare and happiness in this world and in the hereafter. In line with that, da'wah according to the term (semantics), contains the meaning of activities that are coaching as an effort to maintain and improve something that has existed before; and can also be defined as development as an activity that leads to renewal or holding something that does not already exist. Khatib in certain situations are sometimes the same as ulama, who as the informal opinion leader are not only considered as Islamic leaders, but are often treated as leaders of social groups or communities whose influence extends beyond the boundaries of religious areas, penetrates into political, social, political aspects, culture, and government.